The impact of the Sarbanes–Oxley Section 404(b) exemption on earnings informativeness. Issue 1 (12th December 2019) - Lyubimov, Alexey; Davis, Larry; Trompeter, Greg
Abstract : We investigate whether firms who voluntarily drop compliance with Section 404(b) of Sarbanes–Oxley (SOX)—the requirement to have an outside auditor conduct an audit of internal control over financial reporting—suffer a loss of earnings informativeness. Section 404(b) has been widely criticized for imposing costs in excess of the benefits to investors. Calls for wholesale repeal and increasingly wide exemptions from compliance continue to this day. The fact that non‐US regulators have not passed similar regulation outside of the USA appears to be partially driven by similar cost concerns. Our results indicate that voluntary dropping of 404(b) is associated with a drop in earnings informativeness. This result is driven primarily by financially distressed companies. Our results address previous calls for research about the market's perception of 404(b) compliance and suggest that regulators may wish to consider firm characteristics when determining which firms should be required to purchase an audit of internal control over financial reporting.